2023
DOI: 10.1177/10499091231187341
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Palliative Care Knowledge and Symptom Burden Among Female Veterans With Serious Illness: A Cross-Sectional Study

Abstract: Background: The female Veteran population is rapidly growing, as is their use of Veterans Affairs (VA) medical centers (VAMCs). Additionally, 90% of female Veterans are under 65 years old, meaning healthcare providers at VAMCs must be ready to manage the complex serious illnesses that affect female Veterans as they age. These serious illnesses require proper medical management, which can include palliative care. However, little palliative care research includes female Veterans. Aims: The aims of this cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Even with the notable innovation and success of their palliative and hospice care programs across the United States, it begs the question of why these participants described such poor quality of life. This finding was echoed in the quantitative arm of this study with those receiving care at VHA facilities having worse physical symptoms associated with their serious illness than female veterans receiving care at civilian facilities 30 . In addition, female veterans receiving care at VHA facilities have more serious illnesses than those receiving care at VHA facilities, 30 which likely accounts for the poor quality of life described by this study's results.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Even with the notable innovation and success of their palliative and hospice care programs across the United States, it begs the question of why these participants described such poor quality of life. This finding was echoed in the quantitative arm of this study with those receiving care at VHA facilities having worse physical symptoms associated with their serious illness than female veterans receiving care at civilian facilities 30 . In addition, female veterans receiving care at VHA facilities have more serious illnesses than those receiving care at VHA facilities, 30 which likely accounts for the poor quality of life described by this study's results.…”
Section: Discussionmentioning
confidence: 56%
“…This finding was echoed in the quantitative arm of this study with those receiving care at VHA facilities having worse physical symptoms associated with their serious illness than female veterans receiving care at civilian facilities. 30 In addition, female veterans receiving care at VHA facilities have more serious illnesses than those receiving care at VHA facilities, 30 which likely accounts for the poor quality of life described by this study's results. Other studies have suggested that VHA facilities tended to have a higher rate of palliative care consultations within 30 days of death and were more likely to die in dedicated palliative and hospice care units compared with civilian facilities.…”
Section: Journal Ofmentioning
confidence: 83%